Water column biogeochemical data from Mercer Subglacial Lake - Priscu, John; Skidmore, Mark; Dore, John; Hawkings, Jon; Tranter, Martyn; Science Team, SALSA; Steigmeyer, August; Li, Wei; Barker, Joel (IEDA: US Antarctic Program Data Center, 2023)
This dataset contains water column biogeochemical properties measured on discrete samples collected from Mercer Subglacial Lake by the SALSA project. Data included are: specific conductance; carbonic acid system parameters (total alkalinity, total inorganic carbon, and pH); water stable isotopes (δ2H and δ18O); dissolved gases (oxygen, methane, nitrous oxide, and hydrogen); dissolved nutrients (ammonium, nitrite and phosphate), major anions (including nitrate) and cations; size-fractionated colloidal and dissolved trace elements); dissolved organic carbon; and microbial cell and virus-like particle counts.